CAUSAL FACTORS AFFECTING NURSING INFORMATICS LITERACY COMPETENCY OF NURSING STUDENTS - Changpad , Teerawat; Songkram, Noawanit (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2022)
The purpose of this research aimed to study the level of nursing informatics literacy competency and to explore the causal relationship model affecting nursing informatics literacy competency of nursing students. The total research sample was 839 students, who were the 2nd, 3rd and 4th year of nursing students from The Royal Thai Army Nursing College, Royal Thai Navy College of Nursing, Royal Thai Air Force Nursing College, Police Nursing College, and Ramathibodi school of nursing. The instruments for data collection were questionnaires including factors related to nursing informatics literacy competency of nursing students and nursing informatics literacy competency questionnaire. The data were analyzed by using descriptive statistics. Furthermore, the causal relationship model was also analyzed by using LISREL program. The result showed that nursing student had a rather high level of nursing informatics literacy competency (M = 4.15, SD = .68). The causal relationship model of nursing informatics literacy competency of nursing students fitted the data ( 2 (df = 32, N = 839) = 117.36, p = .000, CFI = .997, GFI = .980, AGFI = .936, RMSEA = .056, SRMR = .026). The factors in the model could together explain 54.10 percent of the nursing informatics literacy competency variances of nursing students and have positive direct and indirect influence among all variables. The results of this research provide information for instructors to develop a program to promote nursing informatics literacy competency among nursing students.